Code Review is just reviewing code? A qualitative study with practitioners in industry - Cunha, Atacílio; Conte, Tayana; Gadelha, Bruno (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
Code review is essentially the process of assessing code made by a developer from the perspective of others. Considering the Modern Code Review (MCR) activities within the industry, many opportunities can be evaluated with the practitioners that adopt MCR within everyday software development. Based on that, we evaluated the perspective of software practitioners on code review by applying a survey to understand more about the aspects of MCR in their software development routine. Our qualitative results show that MCR activities are not only about reviewing code but also with knowledge sharing applied at team/project level or between different levels of seniority. We also found other important aspects such as identification of Cognitive Empathy and Career Development related to the MCR process. This research contributes to increase perspective that can be obtained with MCR process applied in the software development industry.